1999
DOI: 10.1152/jappl.1999.86.5.1696
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of stress proteins in rat myocardium after free wheel or treadmill run training

Abstract: High-intensity treadmill exercise increases the expression of a cardioprotective, inducible 72-kDa stress protein (SP72) in cardiac muscle. This investigation examined whether voluntary free wheel exercise training would be sufficient to confer a similar response. Male Sprague-Dawley rats were randomly assigned to either treadmill (TM-Tr) or free wheel (FW-Tr) training groups. By the end of the 8-wk training period, TM-Tr animals ran 1 h/day, 5 days/wk up a 10% grade, covering a distance of 8,282 m/wk. FW-Tr r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
89
4
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 32 publications
13
89
4
2
Order By: Relevance
“…There is little evidence in the literature reporting that exercise training promotes an increase in CS activity in rat cardiac muscle (10). Our findings are consistent with previously published data indicating that CS activity is not altered after endurance training in rat cardiac muscle (1,2,17,18,30). It was suggested that myocardium has sufficient preexisting oxidative capacity to supply the energy requirement during exercise.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is little evidence in the literature reporting that exercise training promotes an increase in CS activity in rat cardiac muscle (10). Our findings are consistent with previously published data indicating that CS activity is not altered after endurance training in rat cardiac muscle (1,2,17,18,30). It was suggested that myocardium has sufficient preexisting oxidative capacity to supply the energy requirement during exercise.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have been conducted to determine the influence of exercise training in the mitochondrial enzyme adaptation in cardiac muscles (2,10,11,18,19). Although the majority of previous studies suggest that the traininginduced alteration of mitochondrial enzymes is not noticeable in cardiac muscle (1,2,17,18,30), a few discrepant results regarding the changes were reported (10). Moreover, among the studies that have been conducted to examine the exercise-induced response of CS in cardiac muscle, very few have provided data regarding the transcriptional, translational, and/or posttranslational processes.…”
mentioning
confidence: 99%
“…Exercise is also a type of stressor that increases the content of HSP72 in mammalian cardiac muscle (7,8) and some evidence indicates that exerciseinduced HSP72 plays a protective role in the mammalian heart against stresses (9).…”
mentioning
confidence: 99%
“…One may expect that wheel running, like other types of running, activates the HPA axis as well as the sympathetic nervous system (Girard & Garland 2002;Makatsori et al 2003;Naylor et al 2005;Droste et al 2006;Fediuc et al 2006;Droste et al 2007;Droste et al 2009a;Droste et al 2009b). However, the extent of activation is much lower in voluntary wheel running because it avoids the excessive stress inherent in forced treadmill running (Noble et al 1999), and mostly involves low-to-moderate resistance with higher repetition (Konhilas et al 2005). Moreover, voluntary wheel running in rodents can be differentiated from other uncontrollable stressors that inevitably involve threat or fear, as it is a predictable, controllable, and rewarding activity.…”
Section: Discussionmentioning
confidence: 99%